Measuring toe clearance using a wireless inertial sensing device - Lai, D.; Begg, R.; Charry, E.; Palaniswami, M.; Hill, Keith (2008)
Tripping and slipping falls are serious health concerns for the elderly because they incur high medical costs and can result in life threatening injuries i.e., internal bleeding. Recently there has been an increased interest in the development of portable inertial sensing devices for measuring human movement. These devices employ acceleration and angular data to obtain limb motion such as velocity and displacement through integration of acceleration values. In this paper, we investigate the performance of a wireless inertial sensing device for monitoring vertical toe clearance during walking. It has been demonstrated that variability in minimum toe clearance (MTC) which occurs during the swing phase is a sensitive falls risk predictor. Our device is composed of a tri-axis accelerometer and dual-axis gyroscope wirelessly connected through the use of Crossbow motes. The vertical toe clearance is obtained through double integration of the resultant acceleration in the vertical direction. We have performed zero base, treadmill and intersubject experiments to investigate device performance to environmental variations and compared the calculated toe clearance against measurements made by an Optotrak motion system. It was found that device outputs were approximately independent of small ambient temperature variations, had a reliable range of 20m indoors and 50m outdoors and a maximum transmission rate of 20 packets/s. Toe clearance measurements coincided with Optotrak measurement trends but suffered from cumulative integration errors over time. The identification, quantification and reduction of these errors are intricate but important further research issues. © 2008 IEEE.